Phenomenological, axiological, and hermeneutical ethics - Quesada Rodríguez, Francisco (2023)
This article explains the origins of phenomenological ethics and its derivations in two complementary perspectives: axiological ethics as the development of a material phenomenology of values and hermeneutical ethics as a phenomenological interpretation of human life in the double ontological dimension of alterity and ipseity. The article follows the development of the phenomenological tradition from its primitive origins to its heretical derivation.